2003
DOI: 10.1189/jlb.1003491
|View full text |Cite
|
Sign up to set email alerts
|

4-1BB-dependent inhibition of immunosuppression by activated CD4+CD25+ T cells

Abstract: 4-1BB (CD137) is a costimulatory molecule involved in the activation and survival of CD4, CD8, and natural killer cells. Although a great deal has been learned as to how 4-1BB-mediated signaling governs the immunity of conventional T cells, the functional role of 4-1BB in the context of CD4(+)CD25(+) regulatory T cell (Tr) activation is largely unknown. Using 4-1BB-intact and -deficient mice, we investigated the effect of the 4-1BB/4-1BB ligand pathway on the suppressive function of Tr cells. Our data indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 33 publications
3
123
3
2
Order By: Relevance
“…In contrast with our study, Choi et al (29) showed that CD137 ligation on Tregs inhibited their suppressive function in vitro without inducing proliferation, whereas stimulation of Tregs with a CD137-Fc fusion protein expanded Tregs but did not manipulate their functions (31). However, the identification of Tregs in Choi et al's study (29) was performed by staining for CD25 surface expression (29). The use of a nonspecific Treg marker such as CD25, which is also expressed on recently activated CD25 + effector T cells, makes the interpretation of the data somewhat complicated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with our study, Choi et al (29) showed that CD137 ligation on Tregs inhibited their suppressive function in vitro without inducing proliferation, whereas stimulation of Tregs with a CD137-Fc fusion protein expanded Tregs but did not manipulate their functions (31). However, the identification of Tregs in Choi et al's study (29) was performed by staining for CD25 surface expression (29). The use of a nonspecific Treg marker such as CD25, which is also expressed on recently activated CD25 + effector T cells, makes the interpretation of the data somewhat complicated.…”
Section: Discussioncontrasting
confidence: 99%
“…CD137 can be constitutively expressed on CD4 + Foxp3 + Tregs (7,29), but whether signaling through CD137 treatment increases suppressive Treg activity, and therefore counteracting antitumor CD4 + T cell responses, is currently unknown (5,(29)(30)(31). Interestingly, we found that CD137 ligation on Tregs increases not only the size of the Treg population but also drives alterations of Treg functions to effector cells in the absence of CD8 + T cells.…”
Section: Discussionmentioning
confidence: 78%
“…Further work in defined in vivo systems of antigen-specific CD4 + T cells is needed to clarify these discrepancies. The recent finding of CD137 on regulatory T cells [61] might hint the research on theses issues. In any case, we have found that anti-CD137 administration following vaccination with RAdNS3 clearly augments CD4 + responses against HCV NS3, and this finding might have important implications for vaccination against HCV infection.…”
Section: Discussionmentioning
confidence: 92%
“…The SF cytokine milieu also contains high local concentrations of IL-15 and IL-12 which down-regulate CD28 but enhance 4-1BB, ICOS and PD-1 expression by CD8 + T cells and increase CD8 + cell survival [23]. CD4 + CD25 + Treg display attenuated regulatory function following 4-1BB expression [24]. As 4-1BB expression was reduced in RA(TNFi), this raises the question as to whether or not it might be a component of the improved suppressor function by CD8 + CD28 − Treg following therapy in RA(TNFi) patients.…”
Section: Discussionmentioning
confidence: 99%